"In México, I was someone, but here I am a nobody:" an immigrant mother and daughter moving beyond love to facilitate new ways of being. Issue 6 (3rd July 2022) - Bauer, Eurydice; Sánchez, Lenny
Abstract: In this article, we present parallel narratives of an immigrant youth and her mother who have had to maneuver continual and abrupt interruptions in family cohesiveness and other daily experiences due to anti-immigrant policies and the materialization of being cast beyond love. We highlight how they created spaces of self-transformational love and coalitional love to resist measures of exclusion and redraw how they participated in a divided world. We also argue how educators must encourage these spaces of love and work against practices that contribute to the alienation and suppression of immigrant students and their families. Rather, educators must put a human face to these human struggles and break free from any pretense that this work should solely occur outside the bounds of a school's borders.